Base-pair substitution hotspots in GAG and GCG nucleotide sequences in Escherichia coli K-12 induced by cis-diamminedichloroplatinum (II). - Brouwer, J (1981)
Cell killing and mutation induction by cis- and trans-Pt(NH3)2Cl2 in Escherichia coli were examined by studying forward mutagenesis in the lacI gene in cells with different repair capacities. Survival experiments showed that repair-proficient cells were slightly more sensitive for the cis isomer than for the trans isomer, whereas repair-deficient RecA and UvrB cells were extremely sensitive only for the cis compound. cis-Pt(NH3)2Cl2 induced mutagenesis in both wild-type cells and RecA cells but not in UvrB cells; whereas no detectable mutagenesis was induced by treatment with the trans compound. Examination of the nature of the mutations induced by cis-Pt(NH3)2Cl2, by using the LacI system, revealed that base-pair substitutions leading to nonsense mutants are only induced in wild-type cells, suggesting that the intact products of both the uvrB and the recA gene are necessary for the repair responsible for this type of mutagenesis. Investigation of the nonsense mutants reveals that 70% of these mutations result from GC leads to TA or GC leads to AT substitutions at sites where the guanine is part of a GAG or GCG sequence. These results are discussed in relation to existing theories on the interaction between Pt compounds and DNA. A model for Pt--DNA adducts, leading to base-pair substitutions, is proposed.